Pengaruh Manajemen Waktu, Motivasi Kerja dan Kinerja Guru Terhadap Kompetensi Profesional Guru - Al Munawwarah, Rofiqah; Bahri, Jamal Bahri (Universitas Islam Negeri Alauddin Makassar, 2022)
This research was carried out by all State Vocational Schools in Soppeng Regency, South Sulawesi Province. In this study, the population is 57 teachers of State Vocational Schools in Kabupaten Soppeng. The sampling technique in this study using Simple random sampling is said to be simple (simple because sampling is done randomly without regard to the existing strata in the population. The data analysis tool used in this study is research with multiple linear regression. Based on the results of the research conducted, it shows that: Time Management has a positive and significant effect on teachers' Professionals in SMKN Kabupaten Soppeng, Teacher Motivation has a positive and significant effect on teacher Professionals in SMKN Kabupaten Soppeng District, Teacher Performance has a positive and significant effect on Professionals Teachers at SMKN Kabupaten Soppeng, Time Management, Work Motivation and Teacher Performance simultaneously had a positive and significant effect on teacher Professionals in SMKN Kabupaten Soppeng.